PENGEMBANGAN MODEL ECOTOURISM DALAM RANGKA PERTUMBUHAN HIJAU DI KABUPATEN WAKATOBI(2013) - Ihsyaluddin Ihsyaluddin (Program Studi Manajemen Lingkungan, 2014)
This research is aim at developingecotourism model to support green growth implementation.The objects of research is describe the potential resources in Wakatobi and to finds a model ecotourism based of ecological to support Green Growth. The research used Research and Development method. Data have been collected by conducting indepth interview, and focus group discussion (FGD). This research reveals that the resources might be potential to develop would ecotourism setting. These researchalso produced somefactors that wouldsupport the development of ecotourism by involving willingness on local community, goodunderstanding on tourism benefit, and no cultural constraints. Also the produced environment equilibrium and social justice.